Staphylococcus aureus colonisation and host-microbe interactions - Sangvik, Maria (University of Tromsø, 2013)
The papers of this thesis are not available in Munin: 1. Maria Sangvik, Renate Slind Olsen, Karina Olsen, Gunnar Skov Simonsen, Anne- Sofie Furberg, and Johanna U. Ericson Sollid: 'Age- and gender-associated Staphylococcus aureus spa types found among nasal carriers in a general population : the Tromsø Staph and Skin Study', Journal of Clinical Microbiology (2011), vol. 49, no. 12:4213-4218. Available at http://dx.doi.org/10.1128/JCM.05290-11 The accepted manuscript version of this paper is available in Munin at http://hdl.handle.net/10037/4077 2. Karina Olsen, Maria Sangvik, Gunnar Skov Simonsen, Johanna U. Ericson Sollid, Arnfinn Sundsfjord, Inger Thune and Anne-Sofie Furberg: 'Prevalence and population structure of Staphylococcus aureus nasal carriage in healthcare workers in a general population. The Tromsø Staph and Skin Study', Epidemiology and Infection (2013), vol.141, no.1:143-152. Available at http://dx.doi.org/10.1017/S0950268812000465 3. Marit Sørum, Maria Sangvik, Marc Stegger, Renate S. Olsen, Mona Johannessen, Robert Skov, and Johanna U. Ericson Sollid: 'Staphylococcus aureus mutants lacking cell-wall bound protein A found in isolates from bacteraemia, MRSA-infection and a healthy nasal carrier' (manuscript). 4. Fatemeh Askarian, Maria Sangvik, Anne-Sofie Furberg, Anne-Merethe Hanssen, Johanna U. Ericson Sollid and Mona Johannessen: 'Staphylococcus aureus TIR-domain protein, TirS, negatively interferes with TLR2-, MyD88- and TIRAP-mediated NF-κB signaling and increases intracellular bacterial accumulation' (manuscript) Why are some people carriers of Staphylococcus aureus while others are not? Is the pathogenesis of S. aureus just a mishap, or is it a well-regulated performance showing us the versatility of this commensal bacterium? Even after all these years of research, we don’t know for sure, and new insights are needed to completely answer these and other questions regarding S. aureus colonisation and infection. As treatment of S. aureus infections can be challenging and may even result in ...